Študentje razrednega pouka in njihovo pojmovanje različnih razsežnosti naravoslovja - Hribar, Simona; Fošnarič, Samo (Revija za elementarno izobraževanje, 2016)
Primary Education Teaching Students and their Understanding of the Various Dimensions of Natural Sciences. The article analyses the viewpoints of students in the study programme Elementary Education on different dimensions of their conception of natural sciences. The research was based on the students of primary school teaching at the Faculties of Education in Slovenia (n=276). We investigated the existence of differences among the first and final year students, the existence of environment-related differences and the correlation among different dimensions. The results were then compared to foreign (USA, South Korea) research findings. We found out different profiles of future primary school teachers were being educated. However, we did not find any major differences in the education of future primary school teachers in Slovenia. We have found out that study programmes of primary school teaching in Slovenia and in different other countries mainly differ in organization, content, structure and balance of individual natural science contents. Such differences could nevertheless have a significant influence on students’ final conception of and on their attitude towards natural science.
Keywords: students; primary shool teaching; faculties of education; science; understanding of science